Strategi Pencegahan Post-Market akan Fenomena Maraknya Kasus Kejahatan Narkotika di Lingkungan Apartemen “X” (Dikaji Melalui Teori Situational Crime Prevention) - Aulia Dwi Adhitya; Mohammad Kemal Dermawan (Dinasti Review, 2024)
The growth of apartment construction in the big cities is increasing year by year. This vertical residential building is not exempt from criminal practices. The number of crimes that occurred, especially drug crimes in apartments, also increased as the construction of high apartments grew. This article will explain the phenomenon of drug crime cases in the apartment neighborhood by focusing on the depiction/discovery of facts related to the real situation, including looking at the social aspects that have influenced the phénomena of drug crimes that occurred in the Apartment. This approach is used to find out how effective prevention efforts, requiring a preliminary in-depth understanding of the problem of crime abuse and drug trafficking in the apartment methods of data collection used are secondary data. Applying the theory of Situational Crime Prevention in the apartment